Construct validity of the UCSD performance-based skills assessment-brief version (UPSA-B) in HIV disease. Issue 6 (2nd November 2018) - Sheppard, David P.; Woods, Steven Paul; Verduzco, Marizela
ABSTRACT: Among individuals living with HIV disease, approximately 60% experience problems with everyday functioning. The present study investigated the utility of the UCSD Performance-based Skills Assessment-Brief Version (UPSA-B) as a measure of functional capacity in HIV. We utilized a cross-sectional three-group design comparing individuals with HIV– associated neurocognitive disorder (HAND) (HIV + HAND+; n  = 27), HIV+ neurocognitively normal individuals (HIV + HAND−; n  = 51), and an HIV– comparison group (HIV−; n  = 28) with broadly comparable demographics and non-HIV comorbidities. Participants were administered the UPSA-B, the Medication Management Test-Revised (MMT-R), and were assessed for manifest everyday functioning and quality of life, as part of a standardized clinical neurocognitive research battery. Results indicated that the HIV + HAND+ group had significantly lower UPSA-B scores than the HIV + HAND–group, but did not differ from the HIV– group. Among HIV+ individuals, UPSA-B scores were significantly related to MMT-R scores, all neurocognitive domains assessed, and education, but the UPSA-B was not related to manifest everyday functioning (e.g., unemployment), health-related quality of life, or HIV disease variables. Findings provide mixed support for the construct validity of the UPSA-B in HIV. Individuals impaired on the UPSA-B may be at increased risk for HAND, but the extent to which it detects general manifest everyday functioning problems is uncertain.